Electrochemical paper-based devices: sensing approaches and progress toward practical applications - Noviana, Eka; McCord, Cynthia P; Clark, Kaylee M; Jang, Ilhoon; Henry, Charles S (Lab on a chip, 2020)
Paper-based sensors offer an affordable yet powerful platform for field and point-of-care (POC) testing due to their self-pumping ability and utility for many different analytical measurements. When combined with electrochemical detection using small and portable electronics, sensitivity and selectivity of the paper devices can be improved over naked eye detection without sacrificing portability. Herein, we review how the field of electrochemical paper-based analytical devices (ePADs) has grown since it was introduced a decade ago. We start by reviewing fabrication methods relevant to ePADs with more focus given to the electrode fabrication, which is fundamental for electrochemical sensing. Multiple sensing approaches applicable to ePADs are then discussed and evaluated to present applicability, advantages and challenges associated with each approach. Recent applications of ePADs in the fields of clinical diagnostics, environmental testing, and food analysis are also presented. Finally, we discuss how the current ePAD technologies have progressed to meet the analytical and practical specifications required for field and/or POC applications, as well as challenges and outlook. Paper-based sensors offer an affordable yet powerful platform for field and point-of-care (POC) testing due to their self-pumping ability and utility for many different analytical measurements.